Narrowed lumen of the right coronary artery in chronic chagasic patients is associated with ischemic lesions of segmental thinnings of ventricles. - Vieira Sambiase, Nadia; Higuchi, Maria Lourdes; Benvenuti, Luiz Alberto (Investigación Clínica, 2013)
Â Thinning of myocardial segments, mainly at the apex and basal posterior region of left ventricle, are frequent lesions in chronic chagasic cardiopathy (CCC), but still without a well determined etiology. Previously we found severe myocardial microvascular dilatation that could cause ischemia in watershed regions. In this study we analyzed whether narrowness in epicardial coronary arteries in CCC might explain these thinned ventricular lesions. Two groups of dilated hearts with similar weights were compared: eleven hearts from patients with CCC versus four hearts from patients with dilated cardiomyopathy (IDCM). As normal controls we studied three non dilated normal weight hearts. There were no atherosclerotic plaques in the main branches of epicardial coronary arteries and cross-sectional luminal areas of proximal and distal segments were histologically measured. It was found that CCC hearts presented a lower mean luminal area in the right coronary artery (RCA) branch than IDCM, in proximal (4.3 Ó 1.4 vs 6.6 Ó 2.0 mm2; p= 0.02) and in distal (1.6 Ó 1.0 vs 3.4 Ó 0.9 mm2; p= 0.01) segments, with no statistical differences with normal hearts (2.7 Ó 1.3 and 1.5 Ó 0.3 mm2) in proximal (p= 0.2) and distal (p=0.11) sections. In conclusion thinning of ventricular wall in CCC patients seems to be ischemic lesions in the peripheral territory irrigated by the right coronary artery, possibly due to a steal phenomenon by the left coronary, induced by micro vessels dilatation.